Subliminal cues bias perception of facial affect in patients with social phobia: evidence for enhanced unconscious threat processing - Jusyte, Aiste; Schönenberg, Michael (Frontiers in Human Neuroscience, 2014)
Abstract Socially anxious individuals have been shown to exhibit altered processing of facial affect, especially expressions signalling threat. Enhanced unaware processing has been suggested an important mechanism which may give rise to anxious conscious cognition and behavior. This study investigated whether individuals with social anxiety disorder (SAD) are perceptually more vulnerable to the biasing effects of subliminal threat cues compared to healthy controls. In a perceptual judgment task, 23 SAD and 23 matched control participants were asked to rate the affective valence of parametrically manipulated affective expressions ranging from neutral to angry. Each trial was preceded by subliminal presentation of an angry/ neutral cue. The SAD group tended to rate target faces as “angry” when the preceding subliminal stimulus was angry vs. neutral, while healthy participants were not biased by the subliminal stimulus presentation. The perceptual bias in SAD was also associated with higher reaction time latencies in the subliminal angry cue condition. The results provide further support for enhanced unconscious threat processing in SAD individuals. The implications for etiology, maintenance and treatment of SAD are discussed.